2012
DOI: 10.1007/s00109-012-0907-y
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted balance of TNF-α and type I/II interferon responses in SLE and RA: how monocytes manage the impact of cytokines

Abstract: Many cytokines are involved in the pathogenesis of autoimmune diseases and are recognized as relevant therapeutic targets to attenuate inflammation, such as tumor necrosis factor (TNF)-α in rheumatoid arthritis (RA) and interferon (IFN)-α/γ in systemic lupus erythematosus (SLE). To relate the transcriptional imprinting of cytokines in a cell type- and disease-specific manner, we generated gene expression profiles from peripheral monocytes of SLE and RA patients and compared them to in vitro-generated signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…Whereas the specificity of ELISAs that detect IFNα has been questioned,13 indirect assessment of IFN activity has been reported to be much more sensitive 14–16. It should be noted that non-specific induction of IFITs and proteins by other IFNs17 and cytokines18 may contribute to this observation.…”
Section: Introductionmentioning
confidence: 89%
“…Whereas the specificity of ELISAs that detect IFNα has been questioned,13 indirect assessment of IFN activity has been reported to be much more sensitive 14–16. It should be noted that non-specific induction of IFITs and proteins by other IFNs17 and cytokines18 may contribute to this observation.…”
Section: Introductionmentioning
confidence: 89%
“…Это может свидетельствовать о том, что нейтрализация TNFa у данных больных способствует повышению экспрессии генов, которые прежде были подавлены TNFa [30]. С другой стороны, повышение биоактивности IFN в процессе терапии РА можно расценивать либо как неблагоприятный симптом, либо как свидетельство неудавшейся попытки подавить воспаление [25].…”
Section: экспрессия фактора некроза опухолей альфа и интерферонов 1 тunclassified
“…Activated peritoneal macrophages play an important role in RA through the release of inflammatory mediators, including TNF-. Although emerging evidence suggest that TNF-plays a central role in the etiopathogenesis of chronic inflammatory and destructive process of RA (Smiljanovic et al, 2012), the etiology and pathogenesis of RA are still not clear up to now. Previous studies have reported that RA has close relation to endoplasmic reticulum (ER) stress (Yamasaki et al, 2007;Shin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%